(untitled) (The Pakistan Development Review, 1985)
Development can be viewed from many angles. To some it means progress in creating a credible and viable political system. Others view it as a process of social modernization. To most economic planners, development is growth in the national income. This paper follows the view that the ultimate aim is the development and utilization of human capabilities. More generally, the human angle should gain a special position among alternative viewpoints in the light of the substantial evidence that strengthening of the capabilities of human beings to produce, choose and innovate is the most effective means of achieving economic, political and social development.